2014
DOI: 10.4025/actascitechnol.v36i2.17554
|View full text |Cite
|
Sign up to set email alerts
|

<b>The effect of β-cyclodextrin in the photochemical stability of propranolol hydrochloride in aqueous solution<b>

Abstract: ABSTRACT. The degradation of propranolol hydrochloride (1-isopropylamino-3-(naphthoxy)-2-propranolol) in an aqueous solution was analyzed when irradiated by light UV, with and without β-cyclodextrin. There was an increase in the compound´s photostability in nanocavity when compared with the drug without the cyclodextrins' cavity. First order kinetic model was employed for the degradation of propranolol in aqueous media and in cyclodextrins' cavity. The kinetic parameter was obtained by the drug´s absorption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…As can be seen, a clear protective effect of HPβCD against the photodegradation of PPN was observed, with a reduction in the % degraded drug after 5 h of exposition to UV(A)–UV(B) radiations by more than 50% compared to the solution containing the drug alone. This result was in agreement with Ansolin et al [ 45 ], who observed a reduction in the PPN photolysis rate thanks to its complexation with βCD as a consequence of the protection of the aromatic system of the drug by the CD nanocavity. We found that the observed protective effect of the drug was more evident during the whole exposition time for the 1:2 drug:HPβCD systems, i.e., when a higher amount of HPβCD was present in the solution.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…As can be seen, a clear protective effect of HPβCD against the photodegradation of PPN was observed, with a reduction in the % degraded drug after 5 h of exposition to UV(A)–UV(B) radiations by more than 50% compared to the solution containing the drug alone. This result was in agreement with Ansolin et al [ 45 ], who observed a reduction in the PPN photolysis rate thanks to its complexation with βCD as a consequence of the protection of the aromatic system of the drug by the CD nanocavity. We found that the observed protective effect of the drug was more evident during the whole exposition time for the 1:2 drug:HPβCD systems, i.e., when a higher amount of HPβCD was present in the solution.…”
Section: Resultssupporting
confidence: 93%
“…The final value of the degradation constant of PPN in the aqueous solution in the absence of HPβCD (−0.0891 min −1 ) was in agreement with Ansolin et al [ 45 ] (−0.0860 min −1 ). As can be seen, a strong reduction in the drug degradation rate was obtained in the presence of HPβCD, and this effect was more evident in the samples containing higher amounts of CD (1:2 vs. 1:1 mol/mol systems).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations